Relative Orbit Stabilization Control for the Agile Satellite under Stochastic Disturbance. (23rd March 2014) - Wu, Xiande; Guo, Fengzhi; Yang, Wenbo; Xu, Jiangtao; Song, Ting
Abstract : This paper investigates the relative orbit control problem for a space communication satellite network. An observer-based state feedback control scheme is developed under the circumstance of faults and disturbance occurring in the sensors and actuators. The validity of sliding mode observer for the satellites' network is deduced and the analysis and proof of the relative orbit stabilization control are completed.